Marketing to Women: How to Understand, Reach, and Increase Your Share of the World's Largest Market Segment - Marti Barletta (USA Dearborn Trade Publishing, 2006)
Why do Best Buy stores offer " Personal Assistants?" Why does MinuteClinic operate in Target and Cub Foods stores? Why does Kimpton Hotels tie in with the national Dress for Success cause? Why is the author of this book called the " godmother" of the new Volvo concept car? In this lively 2nd edition of Marketing to Women, Marti Barletta tells you why corporations are spending more to capture the multitrillion dollar women' s market. Updated success stories, original strategies and applications, and gender-effective advertising " best practices" make this the most comprehensive resource to help professionals create and execute a marketing plan that targets women. An eye-opening new chapter highlights the convergence of the two most significant consumer marketing trends today: the aging of America and the growing financial power of women. Marshalling statistics about inheritance patterns and longevity, Barletta coins the phrase " PrimeTime Women$1!" (B" to show how yesterday' s " little old lady" will be tomorrow' s " Ms. Moneybags," a target for myriad industries- banking, brokerage, insurance, health, real estate, travel, and self-improvement, just to name a few. In Marketing to Women, Barletta reveals:* How and why women reach different brand purchase decisions than men* How to use her proprietary GenderTrends$1!" (BMarketing Model to create strategies and tactics that will win women' s brand loyalty* How to hook women consumers with new products, relevant communications, smart selling techniques, and the right marketing strategies * Why smart marketers will tap into the profitable market of women 50 years and older- the " golden bull' s-eye" of target marketings
Keywords: Marketing; Women consumers; Business; Nonfiction; HRM: Contemporary Issues (HRM2074-N)